HUBUNGAN PENDIDIKAN DAN PENDAPATAN RUMAH TANGGA TERHADAP PENGGUNAAN JAMBAN SEHAT PADA MASYARAKAT DI SEI KAPORO DESA BATANG KUMU KECAMATAN TAMBUSAI - misnani, misnani; Handayani, Eka Yuli; WAHYUNY, romy (AHM Center, 2023)
Clean and healthy living behavior is an effort to implement environmental sanitation that can help maintain public health. Unhealthy community behavior can be seen from the dirty environment, dirty bathing and toilet areas, and poor sanitation. This bad behavior can cause scabies, scabies, DHF, diarrhea and ISPA. Latrines are effective faecal disposal facilities to break the chain of disease transmission. The use of latrines is not only convenient but can protect and improve the health of families and communities. The increasing number of residents which is not proportional to the existing residential area, the problem regarding the disposal of human waste is increasing, from a public health perspective. The need for healthy latrines for the population must be addressed as soon as possible. The purpose of this study was to determine the frequency distribution of the relationship between education and household income on the use of healthy latrines in the community in Sei Kaporo, Batang Kumu Village, Tambusai District. Analytic quantitative research method with cross sectional design. with a total sample of 86 household heads. The sampling technique is saturated sampling. The data collection tool is using a questionnaire. Data analysis test was carried out by univariate and bivariate (Chi-square test). The results of the statistical test obtained a value of p = 0.010, meaning that there was a relationship between education and the use of healthy latrines and for household income, a p value of 0.000 was obtained, meaning that there was a relationship between household income and the use of healthy latrines in the community in Sei Kaporo, Batang Kumu Village, Tambusai District. Suggestions for Midwifery Etc. Study Programs This research can add references regarding the relationship between education and household income with the use of healthy latrines.